Analisis Kesalahan Berbahasa dalam Tugas Mata Kuliah Kelas MBKM Departemen Pendidikan Bahasa Daerah UNY - Sari, Fitriana Kartika; , Mohamad Makincoiri; Agatia Mega Rianda; Sutrisno Siswoyo (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2025)
The MBKM class of the Department of Regional Language Education UNY is attended by students from various language and cultural backgrounds. The lack of mastery of Javanese language is the main factor causing language errors. This study aims to describe the language errors of MBKM class students. The instrument of this research is the researcher himself with the help of data cards. The data studied are words, phrases, clauses, sentences that deviate from the standard rules/paramasastra of Javanese language. The method used is descriptive-qualitative research method of content analysis technique. The data were collected through reading and recording techniques, then analyzed using Miles and Huberman's qualitative data analysis method. The validity used is the credibility test. The results showed that language errors arose due to the imposition of Indonesian elements that were translated into Javanese, lack of vocabulary, and the use of machine translation. In terms of phonology, there are 43% errors in writing vowel phonemes, 36% errors in writing consonant phonemes, 7% errors in adding consonants, 14% errors in reducing consonants. In terms of morphology, there are 32% affixation errors, 26% diction errors, 22% repetition errors and 20% compounding errors. In terms of syntax, there are 67% sentence writing errors, 16% clause writing errors, and 17% phrase writing errors. The results of the study are used as the basis for mapping errors in Javanese language, then it can be implemented as a signpost for writing Javanese sentences for MBKM class students.